2024
DOI: 10.3390/w16030482
|View full text |Cite
|
Sign up to set email alerts
|

A Field Study to Investigate the Hydrological Characteristics of Newly Established Biochar-Amended Green Roofs

Cuong Ngoc Nguyen,
Hing-Wah Chau,
Nitin Muttil

Abstract: Green roofs (GRs) have been researched for decades, yet their implementation remains constrained due to several reasons, including their limited appeal to policymakers and the public. Biochar, a carbon-rich material, has been recently introduced as an amendment to GR substrate to enhance the performance of GRs through reduced runoff volume, improved runoff quality, and increased soil fertility. This paper aims to investigate the impact of biochar amendment on the hydrological performance of newly established G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…Andrenelli et al [15] found higher porosity and lower bulk density, but Lim et al [16] observed an increase in saturated hydraulic conductivity, and Major et al [17] discovered no effect on biochar. An increase in soil retention capacity was observed by Sun et al [18] and Nguyen et al [19]. Contrary, a decrease or no effect, was found by Kameyama et al [20].…”
Section: Introductionmentioning
confidence: 87%
“…Andrenelli et al [15] found higher porosity and lower bulk density, but Lim et al [16] observed an increase in saturated hydraulic conductivity, and Major et al [17] discovered no effect on biochar. An increase in soil retention capacity was observed by Sun et al [18] and Nguyen et al [19]. Contrary, a decrease or no effect, was found by Kameyama et al [20].…”
Section: Introductionmentioning
confidence: 87%